The Prevalence of intestinal parasitic infections among 7-15 year old children in Jahrom, Iran during 2006-7 - Mohammad Hossein Davami; Reyhaneh Roohi; Ali Reza Sadeghi (فصلنامه دانشگاه علوم پزشکی جهرم, 2008)
Introduction:  One of the main reasons of the occuranle of intestinal parasitic infections in Communities is the asymptomatic infections in some people.  Although there are some reports for parasitic infections from specialized laboratories, there is no confirmed data for these infections among children in Jahrom. It is due to low standards of the methods and also low accuracy in epidemiological studies.